(untitled) (Jurnal Bina Praja, 2021)
To stimulate rural development and reduce poverty in rural areas, The Government of Indonesia enacted the policy of Village Fund in 2014. However, a few studies have been conducted to examine this program. This study aims to describe how poverty alleviation goes following Village Fund Program in Indonesia between 2015-2019. The poverty reduction was represented by holistic data, including the number of poor and the improvement of village status through Indeks Desa Membangun (IDM). The analysis is conducted using a descriptive method by dividing the areas into six regions, Sumatera, Java & Bali, Kalimantan, Sulawesi, Maluku & NT, and Papua. The result showed that over five years, the village fund dramatically increases. Moreover, this growth is along with the slight decline in poverty. The researchers found that the decreasing number of poverty from 2015 to 2019 is about 15%. The IDM status for districts/municipalities shows that the status improved from underdeveloped villages in 2015 to developing villages in 2019. Java is the region that contributed to making the status improved either to be developing, developed, or independent. While it is the Papua region known as the region consisting of most of the least underdeveloped villages. Since the goal of this policy in poverty reduction still works slowly, it needs a lot of effort from many levels of government, from the village, regional, and national officials, to cooperatively work together.